2003
DOI: 10.1002/bip.10517
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the transition states of phosphodiester bond cleavage: Insights from heavy atom isotope effects

Abstract: The nucleotides of DNA and RNA are joined by phosphodiester linkages whose synthesis and hydrolysis are catalyzed by numerous essential enzymes. Two prominent mechanisms have been proposed for RNA and protein enzyme catalyzed cleavage of phosphodiester bonds in RNA: (a) intramolecular nucleophilic attack by the 2'-hydroxyl group adjacent to the reactive phosphate; and (b) intermolecular nucleophilic attack by hydroxide, or other oxyanion. The general features of these two mechanisms have been established by ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 79 publications
(138 reference statements)
0
39
0
Order By: Relevance
“…We attribute these differences to the lower experimental temperature and addition of the fluorescein modification in our current study. However, the most significant result of this study is that the observed pK a is much lower than the ionization of a metal-hydroxide, the suggested nucleophile in the reaction Cassano et al 2004).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…We attribute these differences to the lower experimental temperature and addition of the fluorescein modification in our current study. However, the most significant result of this study is that the observed pK a is much lower than the ionization of a metal-hydroxide, the suggested nucleophile in the reaction Cassano et al 2004).…”
mentioning
confidence: 68%
“…Comparative sequence analysis, site-directed mutagenesis, and phosphorothioate-substitution experiments suggest that the highly conserved helix P4 is critical for catalytic activity, but the exact location of functional groups that comprise the ribozyme active site remains undefined (Waugh and Pace 1993;Haas et al 1994;Pace and Brown 1995;Christian et al 2000;Christian et al 2002;Crary et al 2002). RNase P is proposed to catalyze the phosphodiester bond cleavage using a metal-hydroxide as the nucleophile (Cassano et al 2004), although the kinetic and mechanistic details of this reaction are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is an intramolecular nucleophilic attack on the phosphor atom by the adjacent 2=-hydroxyl to yield a phosphorane transition state. A similar attack is described in both enzymatic [16,17] and nonenzymatic [18] reactions of RNA hydrolysis in solution. Furthermore, the phosphorane transition state is welldocumented in the mechanism of RNases [18].…”
Section: The 5=-poo Cleavage Mechanismmentioning
confidence: 83%
“…2,33,[96][97][98] , and references cited therein), as well as countless other systems (e.g. [99][100][101][102] ).…”
Section: Nitrophenyl Phosphate and P-nitrophenyl Sulfate Hydrolysesmentioning
confidence: 99%